2004
DOI: 10.1136/jcp.2003.013227
|View full text |Cite
|
Sign up to set email alerts
|

Immunostaining patterns of myoepithelial cells in breast lesions: a comparison of CD10 and smooth muscle myosin heavy chain

Abstract: Background: Recent studies have reported CD10 expression in myoepithelial cells (MEC) of the breast, supporting its use as a marker to help distinguish invasive breast carcinoma (IC) from ductal carcinoma in situ (DCIS). Aim: To compare the effectiveness of CD10 with smooth muscle myosin heavy chain (SMMHC) in the detection of MEC in benign and malignant breast lesions. Methods: Histological material from 25 patients with DCIS and 21 with IC were immunostained for CD10 and SMMHC. Staining was scored on a scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 20 publications
6
38
2
3
Order By: Relevance
“…This finding is in accordance with werling et al who reported P63 as the most sensitive and specific myoepithelial marker with only a disadvantage of interrupted attaining pattern [11]. Kalof et al also reported that SMMHC is more sensitive marker for myoepithelial cells than CD10 [15]. In concordance with Cheryl et al two immunohistochemical myoepithelial markers should be used specially in papillary breast lesions, and they suggested either Calponin with SMMHC or with P63 because they are the most sensitive myoepthelial markers [10].…”
Section: Discussionsupporting
confidence: 81%
“…This finding is in accordance with werling et al who reported P63 as the most sensitive and specific myoepithelial marker with only a disadvantage of interrupted attaining pattern [11]. Kalof et al also reported that SMMHC is more sensitive marker for myoepithelial cells than CD10 [15]. In concordance with Cheryl et al two immunohistochemical myoepithelial markers should be used specially in papillary breast lesions, and they suggested either Calponin with SMMHC or with P63 because they are the most sensitive myoepthelial markers [10].…”
Section: Discussionsupporting
confidence: 81%
“…5,6 CD10 positivity has also been reported in stromal myoepithelial cells from normal breast tissue and benign myoepithelial tumors. 3,[7][8][9] Several reports indicated that stromal CD10 expression is associated with biological aggressiveness in various epithelial malignancies. 2,5,10,11 In gastric carcinoma CD10-positive stroma correlates with vascular invasion and metastasis.…”
mentioning
confidence: 99%
“…Recent studies have shown strong correlations between CD10 expression in stromal cells and stage of disease. CD10 expression is only physiologically present in the stromal myoepithelial cells of normal breast tissue [10][11][12]. In case of invasive breast carcinoma, the CD10 expression in stromal cells surrounding the infiltrating tumor cells was observed 6.…”
Section: Breast Cancermentioning
confidence: 99%